Early Introduction to Critical Care Medicine: An Elective Course for Second-Year Medical Students - Andrew Luks; Mary King (Association of American Medical Colleges, 2011)
Abstract This resource is the curriculum for an elective course for second-year medical students that provides an introduction to critical care medicine. Created for students who have already finished their cardiovascular and respiratory system physiology and pathophysiology courses, this curriculum is designed to provide an introduction to the basic principles of caring for critically ill patients and to reinforce concepts (e.g., arterial blood gas interpretation) learned in students' core second-year curriculum. The course includes four components: (1) a series of didactic lectures on core topics in critical care medicine (sepsis, respiratory failure, pediatric critical care, trauma critical care, neurocritical care, airway management), (2) in-person learning opportunities (including spending time on morning rounds in the ICU, shadowing residents on call at night in the ICU, and small-group bedside teaching sessions with an attending physician), (3) a group take-home assignment, and (4) active participation workshops on airway management and communicating about prognosis in the ICU. The course has been offered for the past 2 years at our institutions. Fifty students participated in the course in the first 2 years, 21 students in 2009 and 29 students in 2010. When asked to rate the course on a scale from 1 (poor) to 5 (excellent), students gave the course ratings of 4.87 in 2009 and 5.00 in 2010. When asked to compare the class to other elective classes they have had in medical school on a scale from 1 (much worse) to 5 (much better), students reported average scores of 4.40 in 2009 and 4.80 in 2010. Students rated the in-person learning opportunities higher than the didactic sessions. Bedside teaching rounds with an attending ICU physician and shadowing on-call residents received higher ratings than morning rounds in the ICU. This is likely because the discussion on morning rounds was often beyond the students' level of understanding, while the other sessions provided greater opportunities to tailor the teaching to the appropriate level. Informal surveys of residents and attending physicians reported a high level of satisfaction with their student interactions during in-person learning sessions. Additionally, several ICU attending/medical student mentoring relationships resulted from this class experience. Students did comment that the workload in the course was high compared to other elective courses offering the same amount of credit.